Nosocomial lower respiratory tract infections in patients with immunosuppression: a cohort study - Luis Felipe Reyes; Natalia Sanabria-Herrera; Saad Nseir; Otavio T. Ranzani; Pedro Povoa; Emilio Diaz; Marcus J. Schultz; Alejandro Rodríguez; Cristian C. Serrano-Mayorga; Gennaro De Pascale; Paolo Navalesi; Szymon Skoczynski; et al. (Annals of Intensive Care)
Abstract Background This post-hoc analysis of a multinational, multicenter study aimed to describe and compare clinical characteristics, microbiology, and outcomes between immunosuppressed and non-immunosuppressed patients with nosocomial lower respiratory tract infections (nLRTI). The study utilized data from the European Network for ICU-related Respiratory Infections, including 1,060 adult ICU patients diagnosed with nLRTI. Descriptive statistics were used to compare baseline characteristics and pathogen distribution between groups. A Cox proportional hazards model stratified by immunosuppression status was applied to assess 28-day mortality risk, adjusting for disease severity and key clinical variables. Results Immunosuppression was observed in 24.9% (264/1060) of the patients, and oncological conditions were the most common etiology of immunosuppression. Chronic pulmonary and cardiovascular diseases were the most frequent comorbidities. In both groups, Pseudomonas aeruginosa was the predominant microorganism, particularly affecting patients with immunosuppression (25.3% vs. 16.7%, p = 0.032). Cox regression model adjusted for disease severity (SAPS II), polytraumatized status, altered consciousness, and postoperative status, SAPS II remained a strong independent predictor of mortality, with each one-point increase associated with a 2.3% higher risk of death (HR: 1.023, 95% CI 1.017–1.030, p < 0.001). The analysis also revealed significant heterogeneity in mortality risk among immunosuppressed patients, with hematological malignancies, recent chemotherapy, and bone marrow transplantation associated with the highest mortality. Conclusions Immunosuppressed patients had a lower adjusted survival probability compared to non-immunosuppressed patients. Moreover, P. aeruginosa was the most frequently identified etiological pathogen in immunosuppressed patients.